2012
DOI: 10.1177/0190272512451754
|View full text |Cite
|
Sign up to set email alerts
|

Work Values, Early Career Difficulties, and the U.S. Economic Recession

Abstract: We examine how work difficulties in the early career, and the generally deteriorating work conditions associated with the recent U.S. economic recession, shape individuals’ work values. Drawing on panel data from the Youth Development Study, we test whether individuals change their work values in response to concerns about satisfying material needs or the features of jobs that they are able to attain. Results indicate that extrinsic values are weakened in the face of unemployment, as well as reduced job securi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 34 publications
4
65
0
Order By: Relevance
“…This finding echoes previous research by Gibson (2009) suggesting that effort is central when evaluating a person's merit in relation to receiving unemployment benefits in western welfare states. Previous research by Johnson, Sage, and Mortimer (2012) has demonstrated how work values tend to adapt to work situations with people in well-paying and steady jobs valuing extrinsic values such as pay and stability more than people in insecure, or no, current employment. The explanation of this phenomenon termed the 'reinforcement and accentuation model' avoids the psychological distress associated with cognitive dissonance experienced if one's values are not in accordance with one's situation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding echoes previous research by Gibson (2009) suggesting that effort is central when evaluating a person's merit in relation to receiving unemployment benefits in western welfare states. Previous research by Johnson, Sage, and Mortimer (2012) has demonstrated how work values tend to adapt to work situations with people in well-paying and steady jobs valuing extrinsic values such as pay and stability more than people in insecure, or no, current employment. The explanation of this phenomenon termed the 'reinforcement and accentuation model' avoids the psychological distress associated with cognitive dissonance experienced if one's values are not in accordance with one's situation.…”
Section: Discussionmentioning
confidence: 99%
“…They refer to employees' desires to derive satisfaction and interest from the work itself (Johnson, Sage, & Mortimer, 2012;Porter & Lawler, 1968) Questions 10--18 (see the table below; 5-Likert scale) 13 …”
Section: Intrinsic Work Valuesmentioning
confidence: 99%
“…The most widely used approach classifies work values as intrinsic or extrinsic (e.g., Elizur, 1984;Johnson et al, 2007;Schwartz, 1999;Vansteenkiste, Neyrinck, Niemiec, Soenens, De Witte & Van den Broeck, 2007). On the one hand, extrinsic work values reflect employees' preferences toward rewards external to work, such as pay and job security (Johnson et al, 2012). On the other hand, intrinsic work values concern employees' desires to derive satisfaction and interest from the work itself; sources of such satisfaction, for example, can include autonomy, intellectual challenges, and personal growth (Johnson et al, 2012).…”
Section: Work Valuesmentioning
confidence: 99%
See 2 more Smart Citations